A multifunctional porous scaffold with capacities of minimally invasive implantation, self-fitting and drug delivery. (October 2016) - Di, Shubin; Liu, Xian; Liu, Dian; Gong, Tao; Lu, Liuxuan; Zhou, Shaobing
Abstract: Maxillary sinus floor elevation is of frequent occurrence and extremely important for dental implantation. However, how to conveniently implant a synthetic scaffold in the irregular bony cavity of maxillary sinus and simultaneously prompt new bone regeneration is a great challenge in lifting the maxillary sinus floor. Here, we develop a bioactive self-fitting polymer porous scaffold via one-step creation of interconnected pores with controllable size and loading with a bone morphogenetic protein-2 (BMP-2) therapeutic agent inside these pores for the first time. This scaffold can be compressed like a sponge for minimally invasive surgery and return to its original porous structure in response to a temperature of 41 °C for self-fitting into the irregular cavity of a maxillary sinus. Moreover, the loaded BMP-2 possesses a great capacity to accelerate new bone regeneration. Highlights: A bioactive self-fitting polymer porous scaffold is developed via one-step creation of interconnected pores. This scaffold can be compressed like a sponge for minimally invasive surgery. The loaded BMP-2 possesses a great capacity to accelerate new bone regeneration.